A Conceptual Framework For Islamic Gold Monetization: Hybrid Musharakah Model - Hardiansyah (Proceeding International Annual Conference Economics, Management, Business, and Accounting, 2023)
This conceptual paper proposes a hybrid musharakah gold-based refinancing scheme submitted for productive physical gold investments. It answers the product innovation opportunity challenge in Islamic Financial Institutions (IFI) towards bullion bank activity implementation because of Act of Law No. 4 of 2023 about P2SK. This study uses a descriptive qualitative approach of contemporary resource material about fiqh literature from Shariah Standard No. 57 on gold trading and its trading control released by the World Gold Council and AAOIFI, as well as Fatwa DSN MUI for Musharakah refinancing contract, then validated by semi-structured interviews. We use product simulation to present and compare the concept with an existing gold-based pawn contract (Ar-Rahnu). The calculation will be based on the risk-adjusted valuation to protect the initial investment. Eventually, the result shows that this proposed model can be an alternative to productive gold investment and financing methods for its debt-free contract and make gold savings more valuable.